Total reconstitution of active large ribosomal subunits of the thermoacidophilic archaebacterium Sulfolobus solfataricus. - Londei, P (1986)
The large ribosomal subunit of the extremely thermoacidophilic archaebacterium Sulfolobus solfataricus has been reconstituted from the completely dissociated RNA and proteins by a two-step incubation procedure at high temperatures. Successful reconstitution requires a preliminary incubation of the ribosomal components for 45 min at 65 degrees C, followed by a second heat-treatment at 80 degrees C for 60 min. Structural reassembly depends upon high concentrations of K+ (300-400 mM) and Mg2+ (20-40 mM) ions. In addition, complete recovery of subunit function stringently requires the presence of a polyamine, thermine (or spermine). The reconstituted archaebacterial subunits are essentially indistinguishable from the native ones by a number of structural and functional criteria.